PENGARUH GERAK U-TURN TERHADAP KINERJA LALU LINTAS DI JALAN SOEKARNO-HATTA KOTA PAYAKUMBUH - Abrinanda, Viki; Gusmulyani, Gusmulyani; Zulhedi, Zulhedi (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
On a micro basis, there are several efforts to minimize the problem of traffic movement, especially on the safety and comfort on the road, which can be done by installing a median to separate the traffic flow in opposite directions. In planning the median, it is necessary to prepare a median opening that allows the vehicle to change the direction of travel in the form of a reversal movement or termed a U-Turn movement. One of the effects when doing a U-Turn is the speed of the vehicle where the vehicle will slow down and stop. This slowdown will affect traffic flow in the same direction, this circular movement will cause high traffic volume, lower vehicle speed, and higher density on the road. The author took the research location on roads in the West Payakumbuh District, Payakumbuh City, West Sumatra Province which dotted on the Soekarno-Hatta road section, Parit Rantang Payakumbuh City.The purpose of this study is to determine the performance of the road segment and the level of road service equipped with U-Turn facilities, analyze the average travel time of vehicles performing U-Turn, vehicle speed when performing U-Turn and queue lengths for U-Turn activities. To achieve this goal, the 2014 PKJI method was used. From the results of this study, it was found that the average travel time of the largest vehicle when making a u-turn was 12.68 seconds with a vehicle speed of 1.25 km/hour, with a queue when doing a u-turn of 50 meters. With service level C.Keywords: U-turn, travel time, speed, queue, level of service